Conjugated Polymer/Photochromophore Binary Nanococktails: Bistable Photoswitching of Near‐Infrared Fluorescence for In Vivo Imaging. (12th July 2013) - Jeong, Keunsoo; Park, Solji; Lee, Yong‐Deok; Lim, Chang‐Keun; Kim, Jungahn; Chung, Bong Hyun; Kwon, Ick Chan; Park, Chong Rae; Kim, Sehoon
<x xml:space="preserve">Abstract</x> Nanoscopic dense integration between solid‐state emission and photochromism provides nanoprobes capable of photoswitching of bright NIR fluorescence with high on/off contrast, bistability and improved signal identification, being suitable for imaging applications in autofluorescence‐rich in vivo environments. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>